Are Adenomyosis and Endometriosis Phenotypes of the Same Disease Process? - Marwan Habiba; Sun-Wei Guo; Giuseppe Benagiano (Biomolecules, 2023)
In recent literature reviews, we concluded that the possibility that endometrial molecular aberrations are the sole or a necessary determinant of endometriosis and the Tissue Injury and Repair (TIAR) theory are yet to be convincingly proven. Here, we critically examine the theory that adenomyosis and endometriosis represent different phenotypes of a single disease. A common etiopathology for adenomyosis and endometriosis has been suggested because both conditions entail the presence of endometrial tissue at locations other than the lining of the uterus. There are wide differences in reported disease incidence and prevalence and, consequently, in estimates of the coexistence of both conditions. There are some similarities but also differences in their clinical features and predisposing factors. Each condition has a range of subtypes. These differences alone pose the question of whether subtypes of endometriosis and adenomyosis have different etiopathologies, and, in turn, this raises the question of whether they all share a common etiology. It is debatable whether the recognized differences between the eutopic endometrium in adenomyosis and endometriosis compared to those in unaffected women are the cause or the effect of the disease. The finding of common mutations, particularly of KRAS, lend support to the notion of shared predisposing factors, but this alone is insufficient evidence of causation.